A SEVA-based, CRISPR-Cas3-assisted genome engineering approach for Pseudomonas with efficient vector curing - Eveline-Marie Lammens; Daniel Christophe Volke; Kaat Schroven; Marleen Voet; Alison Kerremans; Rob Lavigne; Hanne Hendrix (Microbiology Spectrum, 2023)
ABSTRACT The development of CRISPR-Cas-based engineering technologies has revolutionized the microbial biotechnology field. Over the years, the Class II Type II CRISPR-Cas9 system has become the gold standard for genome editing in many bacterial hosts. However, the Cas9 system does not allow efficient genomic integration in Pseudomonas putida, an emerging Synthetic Biology host, without the assistance of lambda-Red recombineering. In this work, we utilize the alternative Class I Type I-C CRISPR-Cas3 system from Pseudomonas aeruginosa as a highly efficient genome editing tool for P. putida and P. aeruginosa. This system consists of two vectors, one encoding the Cas genes, CRISPR array and targeting spacer, and a second Standard European Vector Architecture vector, containing the homologous repair template. Both vectors are Golden Gate compatible for rapid cloning and are available with multiple antibiotic markers, for application in various Gram-negative hosts and different designs. By employing this Cas3 system, we successfully integrated an 820-bp cassette in the genome of P. putida and performed several genomic deletions in P. aeruginosa within a week, with an efficiency of >83% for both hosts. Moreover, by introducing a universal self-targeting spacer, the Cas3 system rapidly cures all helper vectors, including itself, from the host strain in a matter of days. As such, this system constitutes a valuable engineering tool for Pseudomonas, to complement the existing range of Cas9-based editing methods, and facilitates genomic engineering efforts of this important genus. IMPORTANCE The CRISPR-Cas3 editing system as presented here facilitates the creation of genomic alterations in Pseudomonas putida and Pseudomonas aeruginosa in a straightforward manner. By providing the Cas3 system as a vector set with Golden Gate compatibility and different antibiotic markers, as well as by employing the established Standard European Vector Architecture (SEVA) vector set to provide the homology repair template, this system is flexible and can readily be ported to a multitude of Gram-negative hosts. Besides genome editing, the Cas3 system can also be used as an effective and universal tool for vector curing. This is achieved by introducing a spacer that targets the origin-of-transfer, present on the majority of established (SEVA) vectors. Based on this, the Cas3 system efficiently removes up to three vectors in only a few days. As such, this curing approach may also benefit other genomic engineering methods or remove naturally occurring plasmids from bacteria.